1986
DOI: 10.1073/pnas.83.20.7966
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-dependent regenerative responses in dendrites of axotomized motoneurons in the cat.

Abstract: Ten days after extradural axotomy, partial spikes are found in >20% of cat L7 motoneurons, while 15-21 days after axotomy the incidence increases to 60%. These responses are produced in excitable (hot) spots in the dendrites by synaptic excitation. Intracellular injection of a lidocaine derivative and effective blocker of Na+ channels from within neurons, results in elimination of partial spikes before blocking somadendritic spikes. Partial spikes appear rather abruptly '.10 days after axotomy in our hands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…These changes include altered excitability of the somadendritic compartment and axon initial segment (17,19), which involves Na-dependent electrogenesis (22,23). While these early experiments were interpreted as suggesting a shift in vectorial transport of channels in axotomized neurons (21,24), our results indicate that an altered pattern of gene expression contributes to the electrophysiological changes.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…These changes include altered excitability of the somadendritic compartment and axon initial segment (17,19), which involves Na-dependent electrogenesis (22,23). While these early experiments were interpreted as suggesting a shift in vectorial transport of channels in axotomized neurons (21,24), our results indicate that an altered pattern of gene expression contributes to the electrophysiological changes.…”
Section: Discussioncontrasting
confidence: 37%
“…Abnormal somatodendritic excitability following axotomy is Na dependent (21,22), and it has been suggested that this is due to a shift, following axotomy, in vectorial transport of Na channels (23,24). Recent experiments, however, demonstrated an attenuation of slowly inactivating, TTX-R currents and simultaneous enhancement of rapidly inactivating, TTX-S Na currents in large cutaneous afferent neurons following axotomy (25).…”
mentioning
confidence: 99%
“…Since dendritic and axonal amputations have occurred in our dissociated neurons, a redistribution of Na+ channels onto dendrites, similar to that shown in axotomized vagal neurons (17), might be proposed to explain these results. It is well known that axotomy can affect Na+-dependent action tOther data show that there is a progressive increase in the density of Na+ currents in pyramidal neurons from embryonic day 16 to P19 (14).…”
Section: Discussionmentioning
confidence: 58%
“…Excitability and Na current density are altered in neurons after axonal injury (22)(23)(24)(25). After axotomy, rat DRG neurons display dramatic changes in their TTX-R and TTX-S Na currents and in their Na channel mRNA profile; these changes include an attenuation of TTX-R and enhancement of TTX-S Na currents (21, 26), down-regulation of SNS͞PN3 transcripts and up-regulation of ␣III transcripts (20), and moderate elevation in the levels of ␣I and ␣II mRNAs (27).…”
Section: Introductionmentioning
confidence: 99%